Natural Radioactivity and Radon Exhalation in the Sediment River Used in Sulaymaniyah Governorate, Iraq, Dwellings - Hussein, Adil M. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2018)
The samples, sand and pebble (Sediment River), were collected from their selling places in Sulaymaniyah city, Iraq. Sand and pebble emanate each of 238U, 232Th, 40K, and radon naturally. The radon concentration in the air (Co) and gamma-specific activity (As) of the samples were measured using passive detectors (CR-39) and gamma spectrum analyzer (3 × 3 NaI (Tl) connected to digital spectrum analyzer), respectively. The mean value of the Co ± deviation of the investigated samples was 176.5 ± 6.9 Bq/mᵌ, which is lower than the worldwide value of 300 Bq m− ᵌ reported by the IAEA. However, an anomaly in Co value was found in Tanjaro (Sand) sample. The mean value radon mass exhalation rate (EM) was 10.9 ± 0.5 μBq/kg/h. The second part of the measuring is the gamma-specific activities (As) of each 226Ra, 232Th, and 40K. The As values were ranged (4.3 ± 0.2–22.6 ± 0.2), (1.9 ± 0.1–4.2 ± 0.1), and (39.8 ± 0.2–86.0 ± 0.4) Bq/kg , respectively. The mean calculated value of radium equivalent (Raeq) was 20.2±0.2 Bq/kg. The annual effective dose rate of gamma (Hann) was 0.13 mSv/y. Fortunately, the Hann value of the samples is lower than the world average value of 0.48 mSv/y.